Theoretical study on preference of open polymer vs. cyclic products in CO2/epoxide copolymerization with cobalt(III)-salen bifunctional catalysts - Roznowska, Aleksandra; Dyduch, Karol; Lee, Bun Yeoul; Michalak, Artur (Journal of Molecular Modeling, 2020)
The preference of open chain of growing macromolecule vs. possible cyclic form was examined for the bifunctional cobalt(III)-salen catalyst for the copolymerization of CO2 with epoxides. A variety of possible isomers was considered (resulting from trans/cis-β salen arrangement, different mutual orientation of quaternary ammonium-chains, and possible binding modes). To explore the conformational space, a combined approach was applied, utilizing semiempirical (PM7) MD and the DFT calculations. The preference of the open and cyclic macromolecules attached to the metal center was compared with the corresponding results for isolated model macromolecules, and the systems built of the macromolecule interacting with the tetra-butyl ammonium cation. Result shows that the cyclic structures are strongly preferred for isolated ions, with relatively low cyclization barriers. In the field of positive point charge, the open structures are strongly preferred. For the ions interacting with tetrabutyl ammonium cation, the cyclic structures are preferred, due to delocalization of the positive charge in the cation. For the complexes involving model and “real” Co(III)-salen catalysts, the open structures are strongly preferred. The possible cyclization by dissociation of alkoxide and its transfer to the neighborhood of quaternary ammonium cation is characterized by high activation barriers. Further, the transfer of alkoxide from the metal center to the cation is less likely than the transfer of carbonate, since the metal-alkoxide bond-energy energy is much stronger than energy of metal-carbonate bonding, as shown by ETS-NOCV results. The conclusions are in qualitative agreement with experimental data showing high selectivity towards copolymer formation in the copolymerization processes catalyzed by bifunctional Co(III) salen-complexes. [Figure not available: see fulltext.]
Keywords: bifunctional Co(III) salen catalysts; CO2 / epoxide copolymerization; conformational space; copolymerization vs. cyclization